INFLUENCE OF CHILDREN IN REAL ESTATE FAMILY PURCHASE DECISION-MAKING CONTEXT - I. Kancheva (Trakia Journal of Sciences)
Purpose: Children play a significant role as active participants in different markets through their own spending power. They are also able to exert considerable influence – explicit or implicit - over other family members’ consumer behavior. The combination of various spatial, structural, financial and practical aspects place the purchase of a real estate among the most complex for the family. The objective of the present paper is to reveal the degree and form of children’s influence throughout family real estate purchase decision-making process. Methods: This paper represents the results of an empirical study focused on parental perceptions of children’s influence in a family real estate purchase. Data were gathered using a convenience sample of 286 respondents – 156 men and 130 women from different Bulgarian families. Frequency distributions, analysis of variance, paired samples and independent samples t-test were applied for the aims of the analysis. Results: Children are found to exert moderate indirect influence throughout the family real estate purchase. They are most influential in the final phase of the real estate purchase decision-making process. Although high influence scores are detected in some attributive decisions, children are found least influential over choices related to technical and financial aspects of the purchase.